From Obstacles to Opportunities : Exploring Learners' Challenges in Academic Vocabulary Acquisition at Lukmanulhakeem School, Southern Thailand - Mediena, Yasmin Elfa; Firdaus, Mohammad Iqbal; Rohim, Abdul; Argade, Sanjaya (Jurnal Paedagogy, 2025)
This study aims to identify and analyze challenges faced by sixth-grade students in acquiring academic vocabulary at Lukmanulhakeem School Southern Thailand, as well as formulate strategies that can support the improvement of their vocabulary acquisition. A qualitative descriptive method was employed, utilizing a narrative inquiry design to explore students' experiences and perspectives in academic vocabulary acquisition. This approach was chosen for its ability to capture and analyze personal narratives across temporal and contextual dimensions, thereby providing a comprehensive understanding of the challenges encountered by students. The study involved 42 students from two classes, 6(1) and 6(2). Data were collected through preliminary observations, in-depth interviews, and an analysis of instructional documents. The data analysis technique in this study uses a narrative inquiry design, which includes transcription of data from observations, interviews, documentation, and field notes to ensure the accuracy of the information.Â  The findings indicate that key barriers to vocabulary acquisition include cultural background, socioeconomic conditions, individual differences, and instructional strategies. Additionally, limited access to learning resources among students from economically disadvantaged backgrounds negatively impacts their vocabulary development. This study highlights the importance of context-based teaching methods and the integration of technology as effective strategies for overcoming students' difficulties in acquiring academic vocabulary. These findings contribute to the development of more effective instructional approaches for teaching academic vocabulary at the elementary school level.